Manajemen Rekayasa Lalu Lintas Pembangunan Gedung Kesenian Dr. Ir. Soekarno Kabupaten Jembrana - Maharan, Putu Anjan Savitri; Sembodo, Agus; Prakosa , Dandun (Syntax Literate, 2025)
The construction and operation of Gedung Kesenian Dr. Ir. Soekarno in Jembrana Regency has the potential to cause traffic problems due to its location on the Denpasar-Gilimanuk National Road and near Hasanudin Intersection with high saturation degree (0.799). This study aims to analyze traffic performance and plan mitigation measures during construction and operational phases. The research method used is quantitative analysis including road segment and intersection traffic performance analysis, parking analysis, and trip generation analysis. Construction phase analysis shows poor traffic performance on Jalan Hasanudin due to on-street parking side friction. Mitigation measures include parking regulation on Jalan Hasanudin, successfully increasing average speed to 52.15 km/h, and project vehicle movement management with circulation planning and strict scheduling. During operational phase, estimated trip generation of 80 pcu/hour decreases road and intersection traffic performance. Jalan Hasanudin reaches Level of Service E, and both intersections experience significant delays reaching Level of Service F. Proposed solutions include prohibiting parking on Jalan Hasanudin and intersection optimization through cycle time adjustments, successfully reducing average delays at intersections.